Stress and Coping in Esports and the Influence of Mental Toughness - Poulus, Dylan; Coulter, Tristan J.; Trotter, Michael G.; Polman, Remco (Frontiers in Psychology, 2020)
This study explored stress and coping in esports athletes and the influence of mental toughness (MT), as defined by two prominent conceptualisations: the 4/6Cs and Mental Toughness Index (MTI) frameworks. Participants were 316 esports athletes, ranked in the top 40% of one of five major esports: Defence of the Ancients 2, League of Legends, Counter Strike: Global Offensive, Overwatch and Rainbow Six: Siege. Participants completed the MTI, Mental Toughness Questionnaire 6 (MTQ6), Stress Appraisal Measure, and Brief COPE inventory. Results showed that MT (via both MT frameworks) was associated with perceived control and MTQ6 subscales were associated with stress intensity. MT (both frameworks) was associated with the selection of more problem-focussed and emotion-focussed coping strategies and less avoidance coping strategies. The results indicate there is some overlap between the MT and stress coping process in high performing traditional sports and esports athletes. Finally, the MTQ6 and MTI had low shared variance (20%), suggesting that the two questionnaires appear to measure different aspects of MT.